Disenchantment and the Liberal Arts - Lathangue, Robin (Canadian Journal of Higher Education, 2012)
This paper is an enquiry into the unpredictability of the liberally educated mind. We are all familiar with the value placed on the word critical when it figures prominently in justifications for liberal arts pedagogy, as in “a liberal arts education should foster the capacity for critical thinking.” However, depending on the milieu in which “critical thinking” is habituated, the meaning of the term may degrade into a theoretical conformity and passive assent to established routines which are inevitably expressions of disapproval. This trajectory is described as disenchantment. Its origins are traced to representations of the intellectual as a distinctly secular creature and, in contemporary philosophical developments, associated with political liberalism—both of which, it is argued, are dominated by fear. Drawing on the recent Catholic “Communio” theology of David Schindler as a way to unveil the repressed theologies and hidden ontologies of liberal neutrality, the paper concludes with a brief examination of liberal arts scholarship that is increasingly open to various models of enchantment.